Antidepressant Drugs for Chronic Urological Pelvic Pain: An Evidence-Based Review. (24th January 2010) - Papandreou, Christos; Skapinakis, Petros; Giannakis, Dimitrios; Sofikitis, Nikolaos; Mavreas, Venetsanos
Abstract : The use of antidepressant drugs for the management of chronic pelvic pain has been supported in the past. This study aimed to evaluate the available evidence for the efficacy and acceptability of antidepressant drugs in the management of urological chronic pelvic pain. Studies were selected through a comprehensive literature search. We included all types of study designs due to the limited evidence. Studies were classified into levels of evidence according to their design. Ten studies were included with a total of 360 patients. Amitriptyline, sertraline, duloxetine, nortriptyline, and citalopram are the antidepressants that have been reported in the literature. Only four randomized controlled trials (RCTs) were identified (two for amitriptyline and two for sertraline) with mixed results. We conclude that the use of antidepressants for the management of chronic urological pelvic pain is not adequately supported by methodologically sound RCTs. From the existing studies amitriptyline may be effective in interstitial cystitis but publication bias should be considered as an alternative explanation. All drugs were generally well tolerated with no serious events reported.